2014
DOI: 10.1038/boneres.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α restricts the anabolic actions of parathyroid hormone

Abstract: The hypoxia inducible factors (Hifs) are evolutionarily conserved transcriptional factors that control homeostatic responses to low oxygen. In developing bone, Hif-1 generated signals induce angiogenesis necessary for osteoblast specification, but in mature bone, loss of Hif-1 in osteoblasts resulted in a more rapid accumulation of bone. These findings suggested that Hif-1 exerts distinct developmental functions and acts as a negative regulator of bone formation. To investigate the function of Hif-1α in osteoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…As dipyridamole blocks purine transport into cells via ent1, it is possible that hypoxic transcriptional regulation of adenosine transporters may modulate adenosine regulated bone formation. It has been reported that osteoblast function and bone formation are strongly oxygen dependent (45), and HIF regulates osteoclast-mediated bone resorption and enhances osteoclast differentiation (46) and limits the anabolic effect of parathyroid hormone (47). A2AR expression and function is also regulated by, most notably, inflammatory stimuli (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…As dipyridamole blocks purine transport into cells via ent1, it is possible that hypoxic transcriptional regulation of adenosine transporters may modulate adenosine regulated bone formation. It has been reported that osteoblast function and bone formation are strongly oxygen dependent (45), and HIF regulates osteoclast-mediated bone resorption and enhances osteoclast differentiation (46) and limits the anabolic effect of parathyroid hormone (47). A2AR expression and function is also regulated by, most notably, inflammatory stimuli (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1a directly stimulates osteoclast activity, (72) directly inhibits mesenchymal stem cell (MSC) osteogenic and adipogenic differentiation (71) and blocks the osteoanabolic effects of PTH in mature mouse bone. (73) HIF-1a also induces production of vascular endothelial growth factor (VEGF). In humans, VEGF stimulates MSCs, their osteogenic differentiation, and the subsequent proliferation and survival of osteoblasts.…”
Section: Hypoxia and Bonementioning
confidence: 99%
“…BMP‐7 is involved in improvement of recovery after ischemic insult, promoted endothelial cell survival and induced angiogenesis indirectly by increasing VEGF expression , while a BMP‐7 variant (BMP‐7v) has been shown to inhibit angiogenic endothelial cord formation in glioblastoma multiforme . In ASCs, a recent study has shown that angiogenic genes ( VE‐cadherin , VEGFA and HIF‐1 α) were suppressed when treated with noggin or dorsomorphin, and as a result weakened angiogenesis . In our investigation, ASC co‐culture promoted gene expressions of BMP‐5 and BMP‐7 in ECs.…”
Section: Discussionmentioning
confidence: 51%